Russian Experience in Implementing E-Government Procedures - FILONENKO V. Natalia; SHAKHVOROSTOV I. Georgiy; VOLKOVA G. Anna (Communications of International Proceedings, 2021)
The article deals with the problems of introducing "electronic government" technologies into the activities of public authorities. The authors of the article investigate the key aspects of the transition to online technologies for providing services to citizens of the Russian Federation in the context of digitalization of state and municipal administration. For the purpose of scientific research, the experience of developed countries is considered, which allows creatively adapting the digitalization paradigm into the activities of public authorities in modern society.
Keywords: Electronic government; digitalization; online services